The social unemployment gap in South Africa: Limits of enabling socio-economic redress through expanding access to higher education - Tivaringe, Tafadzwa (Education Policy Analysis Archives, 2019)
The South African government recently adopted an education policy that attempts to achieve socio-economic redress through expanding free university education to first-year students from low-income backgrounds. However, in a country in which structural factors such as race, gender, and age continue to shape labor market outcomes, to what extent can attainment of university education significantly improve the labor market outcomes of historically marginalized groups? To evaluate the limits and possible unintended consequences of this policy intervention, I use nationally representative data from 1994 through 2017 to explore the correlation between a bachelor’s degree and the likelihood of unemployment. Using a logistic regression and predicted probabilities, I show that, despite the existence of a race-based affirmative action policy designed to alleviate structural barriers in South Africa’s labor market, structural factors still significantly attenuate the role of university education in enabling labor force participation among historically marginalized groups. I term the effect of these multi-dimensional structural barriers: the social unemployment gap. These findings suggest that the use of university education as a strategy for socio-economic redress in labor markets characterized by structural asymmetries extending beyond race necessitates the existence of intersectional labor market affirmative action policies.